A beginner's guide to colored pencil drawing realistic drawings in 14 easy lessons! - Watanabe, Yoshiko (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2023)
A Beginner's Guide to Colored Pencil Drawing provides instructions for creating brilliantly realistic drawings featuring rich shadows, bright highlights, smooth gradients, and glowing colors. Learn at your own pace over the course of 14 easy-to-follow lessons!--Amazon.com.